On Fundamentals and Exchange Rates: A Casselian Perspective - MacDonald, Ronald; Marsh, Ian W. (The Review of Economics and Statistics, 1997)
Using an expanded version of the purchasing-power-parity condition we construct simultaneous equation models for three key exchange rates which incorporate meaningful long-run equilibrium relationships and complex short-run dynamics. We show that fully dynamic out-of-sample forecasts from these models are capable of significantly outperforming those of a random walk model over horizons as short as 3 months, and that they are also more accurate than the vast majority of professional forecasts.